2019
DOI: 10.1038/s41374-018-0178-5
|View full text |Cite|
|
Sign up to set email alerts
|

Knockout of α-calcitonin gene-related peptide attenuates cholestatic liver injury by differentially regulating cellular senescence of hepatic stellate cells and cholangiocytes

Abstract: Background: α-Calcitonin gene-related peptide (α-CGRP) is a 37-amino acid neuropeptide involved in several pathophysiological processes. α-CGRP is involved in the regulation of cholangiocyte proliferation during cholestasis. In this study, we aimed to evaluate if α-CGRP regulates bile duct ligation (BDL)-induced liver fibrosis by using a α-CGRP knockout (α-CGRP −/− ) mouse model. Methods: α-CGRP −/− and wild-type (WT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 38 publications
4
24
0
Order By: Relevance
“…To elucidate whether RAMP1 may have a more general role for regulating the expression and/or activity of YAP/TAZ during liver regeneration, chronic liver injury was induced by biweekly injections of the hepatocellular toxin CCl 4 for 4 weeks. The CCl 4 treatment caused a significant upregulation of αCGRP and RAMP1 mRNA levels, but did not affect expression of βCGRP and CLR (Figure S3), confirming earlier studies where increased αCGRP or RAMP1 mRNA expression levels were observed upon bile duct ligation or CCl 4 ‐induced liver cirrhosis 37‐39 . In addition, expression of Gα11, but not of Gαq and Gαs was significantly increased after CCl4 treatment of mice (Figure S3).…”
Section: Resultssupporting
confidence: 87%
“…To elucidate whether RAMP1 may have a more general role for regulating the expression and/or activity of YAP/TAZ during liver regeneration, chronic liver injury was induced by biweekly injections of the hepatocellular toxin CCl 4 for 4 weeks. The CCl 4 treatment caused a significant upregulation of αCGRP and RAMP1 mRNA levels, but did not affect expression of βCGRP and CLR (Figure S3), confirming earlier studies where increased αCGRP or RAMP1 mRNA expression levels were observed upon bile duct ligation or CCl 4 ‐induced liver cirrhosis 37‐39 . In addition, expression of Gα11, but not of Gαq and Gαs was significantly increased after CCl4 treatment of mice (Figure S3).…”
Section: Resultssupporting
confidence: 87%
“…Previous studies have shown that quiescent hepatic stellate cells (HSCs) are capable of transdifferentiation into myofibroblastic HSCs during the progression of liver fibrosis and gain mesenchymal phenotype [26,27]. We also evaluated the expression change of E-cadherin and vimentin in HSCs by co-staining with desmin, the HSC marker [13,23,28]. With the treatment of vimentin Vivo-Morpholino, we observed less co-expression of desmin/vimentin and increased co-localization of desmin/E-cadherin compared to Mdr2 −/− mice, indicating the HSCs are less myofibroblastic with the knockdown of vimentin (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cell viability (>97%) was assessed by trypan blue exclusion. Mouse HSCs were isolated by laser capture microdissection (LCM) using an antibody against desmin (marker of HSCs) [12,22,23].…”
Section: Methodsmentioning
confidence: 99%
“…8e11 Several studies have demonstrated that during the progression of cholestatic liver diseases, cholangiocytes acquire neuroendocrine phenotypes and secrete and respond to several neuropeptides, including a-calcitonin gene related peptide (a-CGRP) and substance P (SP). 9,12 Both a-CGRP and SP are secreted by neuronal and nonneuronal cells, including macrophages, eosinophils, and cholangiocytes. 9,12e15 There is also growing information regarding the role of neurotransmitters and sensory neuropeptides in the regulation of biliary damage and liver fibrosis.…”
mentioning
confidence: 99%
“…9,12e15 There is also growing information regarding the role of neurotransmitters and sensory neuropeptides in the regulation of biliary damage and liver fibrosis. 9,12 For example, the a1-adrenergic receptor agonist, phenylephrine, stimulates biliary proliferation via Ca 2þ -dependent activation of nuclear factor of activated T cells 2 and specificity protein 1. 16 In addition, parasympathetic innervation has been shown to modulate biliary proliferation and apoptosis in the bile duct ligated (BDL) rat model.…”
mentioning
confidence: 99%